Education Between Foreseeing The Future and Requesting Quality and Accreditation - Mohammad Omar Al-Momani (JURNAL PEDAGOGIK PENDIDIKAN DASAR, 2023)
The study aimed to identify the current education system between looking forward to the future and asking for quality and reliability, as the issue of quality and accreditation occupied many educators and specialists in this field from the principle of providing a high degree of reliability for all educational and educational programs and the youth represented in the teacher, the curriculum and the educational environment, whether in the school stage University mother, in addition to the importance of the presence of modern technology in education and its impact on future generations in the future; Where this study came to shed light on the importance of education and its impact on individuals and societies through the introduction of all kinds of educational and technological innovations; The study followed the qualitative analytical approach, which is based on the theoretical research study. This study concluded that it is necessary to work on strengthening education, whether it is school or university, with all that is new in terms of knowledge and modern technologies, whose impact is reflected on students and society as a whole and contributes to the continuity of progress, growth and prosperity of societies